The temporal correlation between positive testing and death in Italy: from the first phase to the later evolution of the COVID-19 pandemic: Time evolution of COVID-19 weekly lethality rate - d'Alessandro, Vincenzo; Balasco, Nicole; Ferrara, Pietro; Vitagliano, Luigi (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: After the global spread of the novel coronavirus disease 2019 (COVID-19), research has concentrated its efforts on several aspects of the epidemiological burden of pandemic. In this frame, the presented study follows a previous analysis of the temporal link between cases and deaths during the first epidemic wave (Phase 1) in Italy (March-June 2020). Methods: We here analyze the COVID-19 epidemic in the time span from March 2020 to June 2021. Results: The elaboration of the curves of cases and deaths allows identifying the temporal shift between the positive testing and the fatal event, which corresponds to one week from W2 to W33, two weeks from W34 to W41, and three weeks from W42 to W67. Based on this finding, we calculate the Weekly Lethality Rate (WLR). The WLR was grossly overestimated ( 13.5%) in Phase 1, while a mean value of 2.6% was observed in most of Phase 2 (starting from October 2020), with a drop to 1.4% in the last investigated weeks. Conclusions: Overall, these findings offer an interesting insight into the magnitude and time evolution of the lethality burden attributable to COVID-19 during the entire pandemic period in Italy. In particular, the analysis highlighted the impact of the effectiveness of public health and social measures, of changes in disease management, and of preventive strategies over time. (www.actabiomedica.it)